Efficacy of disinfection methods and effects on nutraceutical properties in coriander and strawberry - Salgado-Escobar, Irma; Hernández-Rodríguez, Guillermina; Suárez-López, Yael del Carmen; Mancera-Ugarte, Mijaíl Jesús; Guerra-Ramírez, Diana (Revista Mexicana de Ciencias Agrícolas, 2020)
Cultivation conditions and postharvest handling of coriander and strawberries promote their microbial contamination. There are several procedures to disinfect these products, however, it is necessary to establish advantages and disadvantages of their application. The objectives of this work were to compare the effectiveness of some disinfection treatments to reduce the bacterial load in coriander and strawberry and evaluate the antioxidant properties of these foods, before and after disinfection. The disinfection treatments compared were ozone generated in an appliance at a flow of 6.25x10-5 mol min-1 and ozone obtained in the laboratory by an electrolytic reaction at a flow of 7.75x10-7 mol min-1. Likewise, commercial disinfectants based on chlorine dioxide, colloidal silver and two products obtained from citrus extracts were used, one applied after washing with detergent (standardized extract of citrus seeds and glycerin) and the other used directly (citrus seed extract based on lactic and ascorbic acids). After the disinfection treatments, the colony forming unit count was carried out and the characteristic pigments of the disinfected products, the total phenolic content and the antioxidant capacity were determined by the FRAP test. The results showed that the standardized extract of citrus seeds and glycerin proved to be more effective (p< 0.05) to disinfect both strawberries and coriander, as colony forming units decreased by 97 and 99.9%, respectively; however, it reduced the concentration of anthocyanins in strawberries and the antioxidant capacity in coriander.